Motives and Benefits of the Implementation of Quality Management Systems - Ruževičius, Juozas; Sirvidaitė, Jūratė (Ekonomika, 2002)
The main purpose of the article is to determine the motives that encourage the companies to implement quality management systems (QMS) and to evaluate the benefits of the QMS implementation. After the literature analysis the authors have carried out the study about the motives and benefits of the implementation of QMS among the Lithuanian companies that have obtained ISO 9000 certificates. 31 Lithuanian companies (24% of all certified companies) have presented the answers to the prepared questionnaire. The main purpose of the questionnaire was to find out why Lithuanian companies seek the implementation and certification of QMS in accordance with the requirements of ISO 9000 series of standards and what has changed after the QMS implementation. Furthermore the results of the research were compared to the similar studies performed in the other European countries. The performed research revealed that the implementation of QMS mostly results in the benefits of an intangible nature that are internal to the company. Besides, although the main reasons to start implementing QMS are the expectations of the external advantages, the implementation results mostly in the increase of internal benefits such as improvement in the definition of the responsibilities and obligations of the employees, decrease in the nonconformities, better communication among the employees, increased efficiency. The conclusions and recommendations summarize the main concepts of literature analysis as well as the results of the performed research. The authors believe that the results of the study could give useful guidelines to the companies, which are going to implement QMS and could help the companies, which have already implemented QMS to take more advantages of the system.